Developing emplaced performance knowledge in professional symphony orchestras. (1st January 2021) - Kennedy, Jamie
ABSTRACT: During an investigation into learning in professional orchestral performance, space and place was observed to be important to the musicians' development of orchestral practices. Emplacement is advanced here as a useful concept to explain this spatial aspect of orchestral performance knowledge. Originating in sensory ethnographic research, emplacement refers to the process of construing cultural and embodied knowledges within socially negotiated and co-constituted places, such as an orchestral environment. From this perspective, place is a way of constructing understandings of environments that are contingent on individuals' physical locations, movement patterns, and responses to the affordances of their environment. The participant musicians' performance knowledge was found to be emplaced in and around the physical spaces of their specific musical and social environments. Thus, emplacement is put forward as a broadly-based cognitive process that connects bodily perception, environment, and learning by accounting for how individual musicians change their knowledge as they act together.